2016
DOI: 10.14319/ijcto.42.1
|View full text |Cite
|
Sign up to set email alerts
|

Commissioning and quality control of a dedicated wide bore 3T MRI simulator for radiotherapy planning

Abstract: The purpose of this paper is to describe a practical approach to commissioning and quality assurance (QA) of a dedicated wide-bore 3 Tesla (3T) magnetic resonance imaging (MRI) scanner for radiotherapy planning. Methods: A comprehensive commissioning protocol focusing on radiotherapy (RT) specific requirements was developed and performed. RT specific tests included: uniformity characteristics of radio-frequency (RF) coil, couch top attenuation, geometric distortion, laser and couch movement and an end-to-end r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 31 publications
1
27
1
Order By: Relevance
“…RT-specific demands like patient positioning (flat tabletop-inserts) and immobilization devices needed to replicate patient treatment position also affect MR image quality. For example, by using a flat tabletop-insert and coil holder, Brynolfsson et al [9] reported that SNR reduced to 66% whilst Xing et al [10] , had an average SNR decrease of 42%. Batumalai et al [11] , showed that for supine RT-specific imaging of the breast, a switch from the standard diagnostic 16-channel prone coil to an 18-channel surface coil decreased SNR by 41% and 45% for supine flat and supine inclined (10°) respectively.…”
Section: Introductionmentioning
confidence: 99%
“…RT-specific demands like patient positioning (flat tabletop-inserts) and immobilization devices needed to replicate patient treatment position also affect MR image quality. For example, by using a flat tabletop-insert and coil holder, Brynolfsson et al [9] reported that SNR reduced to 66% whilst Xing et al [10] , had an average SNR decrease of 42%. Batumalai et al [11] , showed that for supine RT-specific imaging of the breast, a switch from the standard diagnostic 16-channel prone coil to an 18-channel surface coil decreased SNR by 41% and 45% for supine flat and supine inclined (10°) respectively.…”
Section: Introductionmentioning
confidence: 99%
“…By adding the bellyboards onto an already raised surface of having a flat couch top, it is not surprising that the signal and image quality suffer from reduced image quality. Xing et al demonstrated a 40% reduction in SNR with the use of a RT flat couch top. McJury et al also demonstrated that adding a structure such as the flat couch can lead to a reduction in SNR from 14% to 40%.…”
Section: Discussionmentioning
confidence: 99%
“…The recommendations given by the American Association of Physicists in Medicine 14 and Institute of Physics and Engineering in Medicine 15 provide guidelines for image quality assurance in diagnostic radiology. In a recent work by Xing et al, 16 the authors demonstrated 40% reduction in SNR using a commercially available fibreglass flatbed specifically designed for treatment planning.…”
Section: Discussionmentioning
confidence: 99%